2001
DOI: 10.1111/0162-895x.00264
|View full text |Cite
|
Sign up to set email alerts
|

Inclusionary Discrimination: Pigmentocracy and Patriotism in the Dominican Republic

Abstract: This study explored the nature of racial hierarchy and the connection between racial identity and Dominican patriotism using a questionnaire given to an in situ sample in the Dominican Republic. The analyses compared the contradictory expectations of the "racial democracy" (or "Iberian exceptionalism") thesis and social dominance theory. Results showed that despite the very high level of racial intermarriage in the Dominican Republic, there was strong evidence of a "pigmentocracy," or group-based social hierar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 31 publications
3
37
0
3
Order By: Relevance
“…Though Sidanius, Feshbach, Levin, & Pratto (1997) find a negative correlation between minority identification and U.S. identification (and this finding is quite important for their theory of Social Dominance Orientations), de la Garza, Falcon, and Garcia (1996) discover a positive correlation (more minority group identification is associated with more national identification; see also Sniderman & Piazza, 2002). Similar findings are reported by Sidanius, Peña, and Sawyer (2001), although to a more limited degree. Thus, the literature is muddled on whether identifying with one's group, even when one is a minority, detracts from being able to identify with a superordinate group like the nation.…”
Section: Linking Group Identities With Intergroup Conflictsupporting
confidence: 89%
“…Though Sidanius, Feshbach, Levin, & Pratto (1997) find a negative correlation between minority identification and U.S. identification (and this finding is quite important for their theory of Social Dominance Orientations), de la Garza, Falcon, and Garcia (1996) discover a positive correlation (more minority group identification is associated with more national identification; see also Sniderman & Piazza, 2002). Similar findings are reported by Sidanius, Peña, and Sawyer (2001), although to a more limited degree. Thus, the literature is muddled on whether identifying with one's group, even when one is a minority, detracts from being able to identify with a superordinate group like the nation.…”
Section: Linking Group Identities With Intergroup Conflictsupporting
confidence: 89%
“…Interestingly, many biracial groups (e.g., the AboriginalWhites (Metis) of Canada, Indian-Whites of India, Korean-Whites of Korea, and the Vietnamese-Whites of Vietnam) are perceived as having lower status than both of their parent groups, whereas groups such as the "Coloured" population of South Africa, and the mixed-race populations of South America have come to adopt an intermediate status above their subordinate parent group, but below dominant Whites (Davis, 1991;Sidanius, Peña, & Sawyer, 2001). (Davis, 1991).…”
Section: Historical Treatment Of Biracial Individualsmentioning
confidence: 99%
“…22 Recent survey-based and experimental studies have found evidence of pigmentocracy or a socio-economic hierarchy based on skin color in the region. Sidanius, Peña, and Sawyer (2001), for instance, find clear patterns of group-based hierarchy on the basis of phenotypes in the DR. They conclude that there is a "clear and consensually structured racial hierarchy" (845) in which Dominicans with European phenotypes enjoy greater status and power than Dominicans with African phenotypes.…”
mentioning
confidence: 95%